Консервативные и модернизационные компоненты социокультурной трансформации - Катаев, С. (Социология: теория, методы, маркетинг, 2000)
There is presented the concept of socio-cultural transformations that is based on the idea that current transformations of Ukrainian society could be ? Demonstration of the world development tendencies. Transforming society lives according to two different paradigms: conservative and modern. The socio-cultural split could possibly become of socio-political character. Ukrainian society is interested in support of strong constructive forces and blockade of conservative, panic and destructive ones.